Platelets correlate with false negative T-SPOT.TB results by inhibiting interferon-γ production in T cells via degranulation - Rao, Jiayue; Rao, Yuting; Guo, Yang; Jiang, Mei; Long, Dan; Luo, Qing; Huang, Zikun; Li, Junming (Frontiers in Cellular and Infection Microbiology, 2022)
Background T-SPOT.TB (T-SPOT) is widely used for the detection of Mycobacterium tuberculosis infection by detecting interferon-gamma (IFN-γ) release in T lymphocytes. This assay is performed on peripheral blood mononuclear cells (PBMCs) separated by Ficoll density gradient centrifugation, which often contain some residual platelets. Here, we investigated the impact of platelets on T-SPOT assay and related mechanisms. Methods The correlation between platelet count, platelet-to-lymphocyte ratio (PLR), and the IFN-γ secreting T cells (ISCs) in positive control wells of T-SPOT assay were retrospectively analyzed. T-SPOT assay was performed with un-treated PBMCs, platelets-removed PBMCs, and platelets-enriched PBMCs to confirm the impact of platelets on T-SPOT assay. The activation of platelets and their impact on IFN-γ production in T cells were detected by flow cytometry (FCM). Platelets and T cells were cultured in a mixed culture system and co-culture system respectively, followed by detection of the frequencies of IFN-γ-producing T cells and the levels of intracellular IFN-γ in T cells by FCM. Moreover, the effect of platelet releasate on the T-SPOT assay was evaluated. Results The ISCs in positive control wells of the T-SPOT assay showed a significant decrease with the increase in platelet count. The PLR of the peripheral blood were negatively correlated with the ISCs in positive control wells of the T-SPOT assay. Removal or enrichment of platelets significantly increased or decreased the ISCs and the positive rate of T-SPOT. Inhibition of platelet activation significantly increased the ISCs of T-SPOT. The frequencies of IFN-γ-producing T cells in PBMCs and the levels of intracellular IFN-γ were significantly reduced by the addition of platelets, both in the mixed culture system and the co-culture system. Platelet releasate upon thrombin activation significantly decreased the ISCs of T-SPOT. Conclusions Platelets correlate with negative T-SPOT results by inhibiting IFN-γ production in T cells via degranulation.